Green Waqf as Social Movement: Millennial Participation and Islamic Ecological Activism in Indonesia - Mansur Efendi; Reni Rosari; Akhmad Akbar Susamto; Heru Kurnianto Tjahjono; Claudius Budi Santoso (Universitas Muhammadiyah Surakarta, 2026)
Green waqf offers an innovative philanthropic model that bridges economic development with environmental sustainability. Despite its potential, most existing literature frames it within economic or traditional Islamic paradigms, leaving a gap in understanding its sociocultural dynamics. This study addresses that gap by analyzing the green waqf movement through the lens of social movement theory, focusing on the millennial-driven Bogor Waqf Forest in Indonesia. Employing a qualitative single-case study and hybrid thematic analysis, the research reveals that the green waqf is articulated as an embodiment of Islamic universalism integrated with ecological ethics. This articulation fosters religious and humanitarian motivations that drive millennial engagement. The movement is expressed through participatory, innovative, and digitally mediated waqf practices. These findings highlight a shift from conventional charity to ecologically conscious Islamic philanthropy. Future studies could explore comparative cases or apply quantitative methods to examine the influence of digital literacy on youth participation in green waqf initiatives.